THE FUNCTIONING OF MEMORY AS THE BASIS OF LITERARY CREATION - Voitenko, Elena (Gênero & Direito, 2019)
The aim of the study is broadening the scientific understanding and also changing the traditional research paradigm regarding role of memory in the process of literary creativity. The article attempts to summarize the main results of an experimental study of regulatory memory in the process of literary creativity of preteens. Regulatory functions are defined as a specific aspect of memory manifestation, which is the construction and regulation of activities performed, as opposed to the cognitive functions that provide for storing, transforming, preserving and updating information in the form of reproduction and recognition, which forms the traditional aspect of studying memory. It is established that the regulatory functions in the process of literary creativity is to organize the structural components of this process. The specifics of memory functioning in the structure of the author's and readers' literary creation of schoolchildren are analyzed. As the ways of activating the literary creativity are determined the formation of skills of processing verbal information with a mnemonic purpose, mastering algorithms of logical operations, enriching the active vocabulary, assimilation of the structure of texts of different types. The study provides a theoretical and methodological basis for creating of new development programs for children of all ages.